Dengue Fever Responses in Dhaka City, Bangladesh: A Cross-Sectional Survey - Md. Mostafizur Rahman; Abu Reza Md. Towfiqul Islam; Saadmaan Jubayer Khan; Kamrun Nahar Tanni; Tuly Roy; Md. Rakibul Islam; Md. Alim Al Raji Rumi; Mohammed Sadman Sakib; Masrur Abdul Quader; Nafee-; Musabber Ali Chisty; Farzana Rahman; et al. (Frontiers Media S.A., 2022)
Objectives: This study intends to evaluate the Dhaka city residents' individual views toward DF.Methods: A cross-sectional survey used google forms for collecting data. Python and RStudio were used for data management and analysis. Kruskal-Wallis or Mann-Whitney U test and logistic regression models were performed, where appropriate.Results: In total 1008 individuals participated in a pre-tested KAP survey. More than 20% reported being affected by DF before the survey, where they rated their current places as being moderately safe (43%). In terms of DF control, 65% had good knowledge, and 68% reported good practice, whereas they demonstrated an overall good attitude. The increased knowledge of individuals could contribute to behavioral changes regarding DF. Female residents demonstrated better DF attitudes (OR: 0.69; p < 0.05) and practices (OR: 0.66; p < 0.01) compared to male residents. Mixed unit residents had poor KAP levels. Educational attainment can also play an essential role in enhancing the attitude level.Conclusion: Overall, dengue surveillance activities with sufficient campaigns are required for behavioral change in Dhaka city. This information could be integrated into other DF-affected countries' strategies against dengue outbreaks.